2017
DOI: 10.1002/ieam.1870
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the reliability of ecotoxicological studies: An overview of current needs and approaches

Abstract: USA. The main workshop objectives were to improve the reliability and reproducibility of ecotoxicity studies, improve the use of peer-reviewed studies in regulatory risk assessment of chemicals, and improve the methods used in risk assessments when evaluating single or multiple lines of evidence. ABSTRACTIn general, reliable studies are well designed and well performed, and enough details on study design and performance are reported to assess the study. For hazard and risk assessment in various legal framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 21 publications
0
62
0
Order By: Relevance
“…However, it remains important to ensure the quality of data produced from standardized model systems, while advancing innovative and exploratory ecotoxicological research that may not be intended or amenable to directly be integrated within environmental assessments (Moermond et al 2017). However, it remains important to ensure the quality of data produced from standardized model systems, while advancing innovative and exploratory ecotoxicological research that may not be intended or amenable to directly be integrated within environmental assessments (Moermond et al 2017).…”
Section: Tools For Improving Risk Assessmentmentioning
confidence: 99%
“…However, it remains important to ensure the quality of data produced from standardized model systems, while advancing innovative and exploratory ecotoxicological research that may not be intended or amenable to directly be integrated within environmental assessments (Moermond et al 2017). However, it remains important to ensure the quality of data produced from standardized model systems, while advancing innovative and exploratory ecotoxicological research that may not be intended or amenable to directly be integrated within environmental assessments (Moermond et al 2017).…”
Section: Tools For Improving Risk Assessmentmentioning
confidence: 99%
“…For the purposes of this explanatory note, the fact that a study reported in a study may not be conducted in accordance with Good Laboratory Practice (GLP) does not imply that the study is irrelevant (Moermond et al, 2016). For the purposes of this explanatory note, the fact that a study reported in a study may not be conducted in accordance with Good Laboratory Practice (GLP) does not imply that the study is irrelevant (Moermond et al, 2016).…”
Section: Eligibility/inclusion Criteria To Establish Relevancementioning
confidence: 99%
“…Relevant studies should be appraised in terms of their reliability (EFSA, 2015a; Moermond et al, 2016). Reliability refers to the extent to which a study is free from bias and its findings reflect true facts.…”
Section: Implications For Risk Assessmentmentioning
confidence: 99%
“…However, if every academic researcher had a fundamental knowledge of the regulatory context of their research, there is much that could be done to increase the regulatory relevance of their data, often in small but significant ways. Considerations such as choice of test organism, organism life stage, exposure concentration and duration, and other test conditions can dramatically alter the usability of these studies for regulatory review (Ågerstrand et al ; Moermond et al this issue; Rudén et al this issue). For example, data generated with a tropical species may not be suitable for a risk assessment for a temperate region.…”
Section: Three Areas For Improved Trainingmentioning
confidence: 99%